Nisin Damages the Septal Membrane and Triggers DNA Condensation in Methicillin-Resistant Staphylococcus aureus - Jensen, Camilla; Li, Heng; Vestergaard, Martin; Dalsgaard, Anders; Frees, Dorte; Leisner, Jørgen J. (Frontiers in Microbiology, 2020)
Nisin is applied as a food preservative in processed foods and has potential for being used synergistically with antibiotics for treatment of patients infected by antibiotic-resistant bacteria such as methicillin-resistant Staphylococcus aureus. The present study explored the antimicrobial effect of nisin on S. aureus viability, membrane integrity, and for the first time used super-resolution microscopy to study morphological changes induced in S. aureus cells exposed to nisin. The exposure of S. aureus to 1 x MIC of nisin caused immediate membrane depolarization, and rapid killing, but four hours after nisin exposure re-growth was observed. Super-resolution structured illumination microscopy (SR-SIM) and transmission electron microscopy (TEM) confirmed that nisin damages the cellular membrane and causes lysis of cells. Strikingly, condensation of chromosomal DNA was observed in all cells exposed to nisin, a phenotype not previously reported for this compound. Moreover, cells exposed to nisin were significantly smaller than non-exposed cells indicating the emergence of cell-shrinkage. The strong association of DNA condensation with nisin exposure indicates that nisin interferes with chromosome replication or segregation in S. aureus.